2018
DOI: 10.7759/cureus.3273
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Staged Treatment for Complex Distal Radius Fractures

Abstract: IntroductionDistal radius fractures are common, but the results and complications of treatment with early external fixation and staged open reduction internal fixation have not been previously reported.Materials and methodsPatients who received staged distal radius fracture treatment from 1/1/2008 to 12/31/2015 at the University of Alabama at Birmingham were identified. Patient, injury, and treatment characteristics, as well as complications, were collected from the medical record.ResultsThere were 50 fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…In fact, every patient with a diagnosis of diabetes who developed an SSI had poor glycaemic control (HbA1c >7) in the perioperative period. The current literature corroborates our findings that a diagnosis of diabetes alone is not clearly associated with SSI after surgery on distal radial fractures (Ficke et al., 2018; Koehler et al., 2015; Zumsteg et al., 2014). In the preoperative assessment of risk of SSI in patients, it is probably more valuable to measure the level of glycaemic control than to classify them simply as diabetic versus non-diabetic.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In fact, every patient with a diagnosis of diabetes who developed an SSI had poor glycaemic control (HbA1c >7) in the perioperative period. The current literature corroborates our findings that a diagnosis of diabetes alone is not clearly associated with SSI after surgery on distal radial fractures (Ficke et al., 2018; Koehler et al., 2015; Zumsteg et al., 2014). In the preoperative assessment of risk of SSI in patients, it is probably more valuable to measure the level of glycaemic control than to classify them simply as diabetic versus non-diabetic.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study of 417 distal radial fractures by Hess et al (2020), smoking was not found to be associated with SSI, although it was associated with other complications. In a study of 50 distal radial fractures treated in a staged manner by Ficke et al (2018), more infections occurred in smokers but the results were not statistically significant.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…CDRFs are high-energy injuries with severe articular disruption, high degrees of comminution, ligamentous instability, and neurovascular injury. 4, 5 Neurological complications are rarely accompanied by distal fracture radius, yet median nerve injury has been reported in 5% to 7% of cases of this fracture. 6 Direct injury of the median nerve after distal radius fracture is unusual.…”
Section: Introductionmentioning
confidence: 99%